Effects of doping on electronic structure and correlations in carbon peapods. - Ge, L; Jefferson, J; Montanari, B; Harrison, N; Pettifor, D; Briggs, G (2009)
Sc@C(82) peapods, which form encapsulated spin-1/2 antiferromagnetic chains under doping with electrons or holes are investigated using hybrid density functional theory. The narrow fullerene bands become shifted relative to nanotube bands resulting in charge transfer and conducting channels along both the fullerene chain and the nanotube. This is accompanied by a reduction in the magnetic moments on the fullerenes, consistent with a 1D Hubbard-Anderson model description.